Oxygen enrichment protects against intestinal damage and gut microbiota disturbance in rats exposed to acute high-altitude hypoxia - Ma, Qianqian; Ma, Jiaojiao; Cui, Jinxiu; Zhang, Chenxu; Li, Yuanzhe; Liu, Juan; Xie, Kangning; Luo, Erping; Tang, Chi; Zhai, Mingming (Frontiers in Microbiology, 2023)
Acute high-altitude hypoxia can lead to intestinal damage and changes in gut microbiota.Sustained and reliable oxygen enrichment can resist hypoxic damage at high altitude to a certain extent. However, it remains unclear whether oxygen enrichment can protect against gut damage and changes in intestinal flora caused by acute altitude hypoxia. For this study, eighteen male Sprague-Dawley rats were divided into three groups, control (NN), hypobaric hypoxic (HH), and oxygen-enriched (HO). The NN group was raised under normobaric normoxia, whereas the HH group was placed in a hypobaric hypoxic chamber simulating 7000 m for 3 days. The HO group was exposed to oxygen-enriched air in the same hypobaric hypoxic chamber as the HH group for 12 hours daily. Our findings indicate that an acute HH environment caused a fracture of the crypt structure, loss of epithelial cells, and reduction in goblet cells. Additionally, the structure and diversity of bacteria decreased in richness and evenness. The species composition at Phylum and Genus level was characterized by a higher ratio of Firmicutes and Bacteroides and an increased abundance of Lactobacillus with the abundance of Prevotellaceae_NK3B31_group decreased in the HH group. Interestingly, after oxygen enrichment intervention, the intestinal injury was significantly restrained. This was confirmed by an increase in the crypt depth, intact epithelial cell morphology, increased relative density of goblet cells, and higher evenness and richness of the gut microbiota, Bacteroidetes and Prevotellaceae as the main microbiota in the HO group. Finally, functional analysis showed significant differences between the different groups with respect to different metabolic pathways, including Amino acid metabolism, energy metabolism, and 2 metabolism. In conclusion, this study verifies, for the first time, the positive effects of oxygen enrichment on gut structure and microbiota in animals experiencing acute hypobaric hypoxia.